THE STUDY OF INDONESIA’S READINESS TO COPE WITH DEMOGRAPHIC BONUS: A REVIEW OF POPULATION LAW - Edie Toet Hendratno; Rachma Fitriati (Journal of Indonesian Economy and Business (JIEB), 2015)
The shift from a population mapping to investigate the population bonus on demographic aspect enhances the economic value this study might contribute for. Indonesian population as the fourth largest number requires some policies to cope with the millennium challenges. Improving nationwide database maintains government on-going strategy to manage its population that is expected to serve all stakeholders for any quest towards economic development. The study uses mixed method with the explanatory sequential strategy. The qualitative approach is used, using social network analysis, supported by desk study, in-depth interview, focus group discussion, and literature studies. This study attempts to provide for improvement to the extant regulations on identity card, mostly electronic-KTP. Demographic bonus is an interesting topic given that the younger the population, the higher the employment demand rate will be. Having systematic database bank and access is expected to alleviate the challenge on high population growth rate in Indonesia. Besides, recommendations are addressed to the policy maker (the Government), mostly on the review or amendment of the extant regulations that might not in line with the database systematic improvements. The study is a primary thesis from a review of population law, using multidisciplinary approach, i.e. population economics (demography), legal study, and public policy that can be used as a testing basis to answer further demographic bonus from an exploration of other scientific inquiries.Keywords: demographic economy, demographic bonus, population administration law, e-ID, social network analysis